2016
DOI: 10.1016/j.polymdegradstab.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Coupled hydro-mechanical aging of short flax fiber reinforced composites

Abstract: One of the challenges in the widespread use of biocomposites for engineering applications is the influence of environmental conditions on their mechanical properties, particularly for a combination of aging factors such as temperature, moisture, and mechanical stresses. Thus, the purpose of this paper is to study the influence of coupled aging factors by focusing on a 100% bio-based and biodegradable composites made of flax/poly(lactic acid) with several fiber contents. The development of a specific testing se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As mentioned previously, aging of materials is associated with a number of property changes, and some polyurethane systems have demonstrated spectroscopic indicators of these changes in addition to loss of physical properties [12][13][14][15][16][17][18]. Acceleration of porous, segmented polyurethane aging was shown to decrease hydrogen bonding as a result of rearrangement of the hard segments.…”
Section: Introductionmentioning
confidence: 79%
“…As mentioned previously, aging of materials is associated with a number of property changes, and some polyurethane systems have demonstrated spectroscopic indicators of these changes in addition to loss of physical properties [12][13][14][15][16][17][18]. Acceleration of porous, segmented polyurethane aging was shown to decrease hydrogen bonding as a result of rearrangement of the hard segments.…”
Section: Introductionmentioning
confidence: 79%
“…The hydrophilic nature of the fibres (with resultant water uptake) and the poor fibre-matrix bonding were also other significant factors that contributed to the reduction of the mechanical performance. Regazzi et al [17] examined the influence of thermohydromechanical-based ageing on the elastic behaviour of flax/poly (lactic acid) composites. The results confirmed that the ageing temperature in wet conditions led to a loss of the elastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…When the temperature increases more than 55 0 C it showed major negative effects so it is recommended to utilize the hybrid composite for lesser temperature application. Aging behaviour of flax fiber composite on their mechanical properties was reported [25]. The major effects due to the environment manipulate of the Fiber is mainly squabble about the mechanical stress, temperature and moisture, this study helped to understand the behaviour of flax with lactic acid for different percentage.…”
Section: Mechanical Property Evaluation and Its Characterizationmentioning
confidence: 79%